(3GdTQM GdcGed ddRjL GdTGeds - (3SjO MSf Hf SjO Ydj GdJhefGJis; (3CHh GdhaG eMeO Hf eMeO, GdHhRLGfjs
(3ChdgG (B:s
(3HYO GdOjHGLg deG QCjJ GdBbQGf ai gPG GdReGf JHGOQhG Edi GMQGR bUHGJ Gdfjd HeG CQGOhG s
(3BNQgG (B:s
(3aEf Bgdfi GdReGf hjSQfi Gddg JYGdi Md gPG GdehVY CLYdg ai ajd gPG GdcJGH s
(3Gda SfI (B821(3g`s
(3ai ahJhZQGajg GdeNWhW GdYQHi Qbe (B2530 (3GdeMahX HHGQjSs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
- (3GdLRA (B1 - (3U (B13 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B400 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B69 s
Keywords: (3Gdadcs